2010
DOI: 10.1111/j.1439-0523.2010.01821.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a potato seedling assay to screen for resistance to Verticillium dahliae

Abstract: A seedling assay was developed for Verticillium wilt (VW) resistance in potato to provide efficient and rapid screening to identify resistant clones in segregating populations. The method provides uniform inoculum, which may reduce false negatives and the confounding effect of late maturity in field-grown plants. Seedlings of two cultivated varieties, five wild potato families and five families of complex hybrids were tested for VW symptoms after exposure to fungal suspensions and exudate from liquid cultures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Although it has been reported that V. dahliae assays performed in greenhouse conditions can be used to predict field performance, results from this study suggest that rootstock reactions to this pathogen in the field may not always be consistent with reactions in the greenhouse. Factors contributing to the observed differences between field and greenhouse studies may include the differing light, water, and temperature levels in the two environments, as well as the presence of additional disease organisms in the field (Bae et al, 2011). In this study, temperatures during the field study were 16°C on average, with 22°C maximum and 11°C minimum, and RH was 81%, whereas in the greenhouse, average temperature was 22 and 21°C in 2014 and 2015, respectively (24°C maximum and 20°C minimum for both years), and RH was 40% and 42%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it has been reported that V. dahliae assays performed in greenhouse conditions can be used to predict field performance, results from this study suggest that rootstock reactions to this pathogen in the field may not always be consistent with reactions in the greenhouse. Factors contributing to the observed differences between field and greenhouse studies may include the differing light, water, and temperature levels in the two environments, as well as the presence of additional disease organisms in the field (Bae et al, 2011). In this study, temperatures during the field study were 16°C on average, with 22°C maximum and 11°C minimum, and RH was 81%, whereas in the greenhouse, average temperature was 22 and 21°C in 2014 and 2015, respectively (24°C maximum and 20°C minimum for both years), and RH was 40% and 42%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To identify verticillium wilt-resistant rootstocks, an efficient disease evaluation system is needed. Field assays can be used for this purpose, but they tend to be lengthy and confined to each growing season's constraints (Bae et al, 2011). Greenhouse assays, however, are rapid and can be conducted most times of the year.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the interaction between progeny and selection methods was not significant, we can confirm that the inoculation method was effective in screening for resistant genotypes regardless of the genitors used. On the other hand, resistance mechanisms working before the entrance of the conidia into the root xylem are also overlooked when using the root dip inoculation method; therefore, an efficient method involving the infection of plants by microsclerotia would be of much interest, as has been developed for other species (Steventon et al, 2002;Bae et al, 2011). However, these methods usually require more time than root dip inoculation to observe symptoms.…”
Section: Influence Of the Inoculation Methods On The Selection Of Res...mentioning
confidence: 99%